The Association Between Adverse Childhood Experiences, Neuropsychological Deficits, and Experiences of Exclusionary Discipline in Early Childhood - Novak, Abigail (Journal of developmental and life-course criminology, 2022)
Recent policy briefs have drawn attention to the use of exclusionary discipline in early learning settings; however, little is known about child-level correlates associated with risk of exclusion. This omission is important, as early childhood education may reduce the likelihood of later delinquent and criminal behavior. Additionally, exclusion from early learning may label a child as deviant, contributing to an accumulation of disadvantage that may place the child at greater risk for delinquency and crime over the life-course. The current study applies Moffitt’s (1993) life-course theory to better understand child-level correlates associated with exclusionary discipline in early childhood. Using data from the 2016 National Survey of Children’s Health (N = 5876), results indicate neuropsychological deficits in early childhood are associated with a 1.38 unit increase in odds of removal from early learning environments. Furthermore, in support of Moffitt’s (1993) interactional hypothesis, exposure to adverse experiences (ACEs) was found to moderate the association between neuropsychological deficits and odds of exclusion, such that children with more indicators of neuropsychological deficits and a greater number of ACEs were more likely to experience exclusion than those with fewer ACEs. Implications for policy and directions for future research are discussed.